Fishery management as a governance network: Examples from the Gulf of Maine and the potential for communication network analysis research in fisheries - Hartley, Troy W. (Marine policy, 2010)
It has been suggested that the fisheries management process with multiple, informed stakeholders and socio-economic, political, and scientific complexity can be considered a governance network. This exploratory study applied communication network analysis (CNA) measures and methods to assess two cases of US federal fishery management in the Northwest Atlantic—Atlantic herring and sea scallop. Through questionnaires and interviews, CNA maps were constructed and quantitative measures of network structure and function (density, weighted average path length) and centrality measures for individual network members (degree, betweenness) were derived using InFlow software. The results show that fishery governance networks are horizontally and vertically integrated across levels of government and public–private–nonprofit sectors. The findings validated existing understanding of fisheries management as a contested, competitive management context among stakeholders, and provided new insights about the effectiveness of information sharing across the network and the critical role of bridgers connecting disparate subgroups. Fisheries management can be conceptualized and analyzed as governance networks, and the paper discusses additional research questions, refinements needed for application of the research methods, and ramifications for managers (e.g., can resource managers manage networks).